Effect of Genotype × Environment Interaction for Seed Traits in Winter Oilseed Rape (Brassica napus L.) - Alina Liersch; Jan Bocianowski; Kamila Nowosad; Katarzyna Mikołajczyk; Stanisław Spasibionek; Franciszek Wielebski; Marcin Matuszczak; Laurencja Szała; Teresa Cegielska-Taras; Katarzyna Sosnowska; Iwona Bartkowiak-Broda (Agriculture, 2020)
Brassica napus (L.), winter oilseed rape (WOSR) or canola, is one of the most important oilseed crop species of the moderate climate zone. Improving the seed quality and yield makes the main target in breeding programs worldwide. In this study, we examined the genotype-by-environment (G×E) interaction with respect to six seed traits among 25 WOSR genotypes. The plant material included the registered canola cultivars, our newly developed mutant breeding lines and the Ogura F1 hybrids and their parental components, in addition to our domestic breeding lines including two semi-resynthesized (semi-RS) lines. The 25 genotypes were examined in field trials at two locations, in three growing seasons. Seed oil and protein content, total glucosinolates (GLS) content in seed meal and C18 unsaturated fatty acid (oleic, linoleic and linolenic) composition in seed oil were examined. The additive main effects and multiplicative interaction (AMMI) analyses revealed significant effects of both, genotype (G) and environment (E) as well as the G×E interaction regarding the analyzed seed traits. In our study, two Ogura F1 hybrids, a CMS line and a new high oleic mutant breeding line revealed high stability and good average values for most of the analyzed seed traits, thus making a valuable source of starting materials for further improvement.